ANALISIS PENERAPAN METODE ACTIVITY BASED COSTING (ABC) DALAM MENENTUKAN HARGA POKOK KAMAR PADA HOTEL ASTON SAMARINDA - Syazili, Wahyumilanda Ifnu (EKONOMIA, 2019)
The purpose of this study was to identify the Hotel Rooms Base Cost Determination by applying Activity Based Costing can be used as a reference in stipulating the base price of hotel rooms at Hotel Aston Samarinda, and as a means of comparison instrument with the current base price of hotel rooms are set over the years, as well as being one of input which provides information on the ABC method, especially in its application to services company, namely hospitality. The analytical method used is comparative descriptive method that analyzing the current base price of hotel rooms at present, is to set the cost method based on the ABC method with its realization. The results of this research indicated that base cost of hotel rooms calculating by applying ABC method when it’s compared with the current base price hotel rooms allowed by hoteliers, the ABC method provides greater results for all room types. This is because the charges on each product. In the ABC method, the cost of each product is charged to a lot of cost driver, so that the ABC method of cost allocation going to the activity of each type of room appropriately based on the consumption of each activity.